(untitled) (EAAE Annual Conference Proceedings, 2024)
We propose this paper as a response to the conference panel topic Design. LESS revolves around the concept of the “non-finito” and effects of unfinish- edness as an important aesthetic condition for contemporary architectural projects. It briefly formulates a theoretical background for a conceptual relation of unfin- ishedness, refinement and wholeness in order to then outline an architectural strategy, which in turn is based on the combination of disciplinary knowledge and computational methods. The processes and results described point to an architecture that continues a long tradition of both appreciation of found conditions and elaborate methods for iterative refinement. We propose a design approach based on the increas- ing scarcity, or ‘less-ness’, of materials that favors the aesthetic richness of trac- es, imperfection and unfinishedness over the modernist concept of the pristine, perfect and novel.